Conducta obstétrica en paciente con embarazo de multiparidad. - Morejón Villamar, Diana Magdalena (2022)
Multiparity is considered one of the most important risk factors with regard to maternal-fetal-neonatal health, it is associated with perinatal entities of high severity and of greater weight in terms of Public Health, such as maternal death, feto-neonatal morbidity, severe maternal morbidity and other types of complications. The present clinical case deals with a 20-year-old patient, thirty-pregnant with no pathological history, who attends an emergency referred from Ricaurte in an ambulance, ECU 911, presenting pain in the hypogastrium radiating to the lumbosacral region of moderate intensity with 12 hours +/-, conscious and oriented in time and space, afebrile and Glasgow 15/15. Faced with this situation, it is necessary to provide the pertinent care to avoid risks that lead to unfavorable results, taking into account the guidelines of the Clinical Practice Guide for Pregnant Women, in such a way that the patient in this case receives quality care.